Energy security in ASEAN region: A case study of Malaysia energy security performance with renewable energy implementation - Sahid E.J.M.; Sin T.C. (Penerbit Akademia Baru, 2023)
The robust economic growth experienced by the ASEAN region in the past decades were mainly due to the progress of industrialization and motorization. Nevertheless, the economy is expected to expand further for the next few decades for the same cause. The primary energy supply is expected to increase at least two-fold in the next two decades from 2015. Hence, an increase of energy requirement in the region will necessitate some of the energy demand to be met through imported energy sources from neighbouring country. The dependency of energy import resources will give a signal to policy makers to address the burgeoning concerns of the energy issues in the region for the few decades to come. Therefore, revising existing and formulating new policies are crucial to improve the energy supply security of the region. In this paper, the analysis indicates that the share of fossil fuels in IEEJ's projection for ASEAN's primary energy supply is projected to be maintained around 80% between 2015 and 2050. Indonesia, Malaysia and Thailand will experience increase of net oil import by at least two-fold. This paper looks into the challenges of the energy security in Southeast Asia by identifying the energy gaps challenges on the availability of energy resources and the energy supply and demand projection up to 2050. This paper discusses on the issues on energy governance in the region for the purpose of enhancing its energy security level. Finally, a Malaysia case study is presented in the paper. 2019 PENERBIT AKADEMIA BARU.